Bimbingan Karir untuk Peserta Didik di Sekolah Dasar - Rohmah, Umi (IAIN Ponorogo, 2018)
The importance of counseling guidance services in elementary schools is motivated by impacting of science and technology development and the society demand who hope that students are equipped with skills. The introduction of career insight is a strategic choice in preparing a generation that is resilient and ready to compete. Standards of Independence Competency (SKK) of students in elementary school with aspect of career development and readiness include the fields of recognition, accommodation and action. The purpose of providing career counseling guidance services, that are: 1) recognizing the types and characteristics of work types, 2) determining ideal goals and plan for the future, 3) explore the direction of work, and 4) adjust skills, abilities, and interests with this type of work. Career guidance material for elementary school students is contained in the Guidance and Counseling Guidance Book published by the Ministry of Education and Culture of the Republic of Indonesia. Career counseling guidance activities are carried out with various methods, including Career Guidance Packages, Instructional, Unit Teaching, Career Day, and Career Field Trips. Career guidance services if in the classroom using Instructional methods that are integrated with the learning process.ÙØ§Ù ÙØ¬ÙØ¯ Ø®Ø¯Ù Ø© Ø§ÙØªÙØ¬ÙÙ ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¦ÙØ© Ø¨Ø®ÙÙÙØ© Ø¢Ø«Ø§Ø± ØªÙØ¯ÙÙ Ø§ÙØ¹ÙÙÙ ÙØ§ÙØªÙÙÙÙÙØ¬ÙØ§ ÙÙ ØªØ·ÙÙØ¨Ø§Øª Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙÙÙ Ø£Ù ÙÙØ²ÙÙØ¯ Ø§ÙØ·ÙØ§Ø¨ Ø¨Ø§ÙÙ ÙØ§Ø±Ø§ØªØ ÙØ§ÙØªØ¹Ø±ÙÙ Ø¨Ø§ÙÙ ÙÙØ©. ÙÙØ°Ø§ ÙÙ Ø®ÙØ§Ø± Ø§Ø³ØªØ±Ø§ØªÙØ¬Ù ÙÙ Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙØ¬ÙÙ Ø§ÙÙÙÙ Ø§ÙÙ Ø«Ø§Ø¨Ø± ÙØ§ÙÙ Ø³ØªØ¹Ø¯Ù ÙÙÙ ÙØ§ÙØ³Ø©. ÙÙ Ø¹ÙØ§Ø± ÙÙØ§Ø¡Ø© Ø§ÙØ§Ø¹ØªÙ Ø§Ø¯ Ø¹ÙÙ Ø§ÙÙÙØ³ ÙØ·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙÙÙ Ø§Ø¡ Ø§ÙÙ Ø¹Ø±ÙÙ ÙØ§ÙØ§Ø³ØªØ¹Ø¯Ø§Ø¯ Ø§ÙÙ ÙÙÙ ØªØØªÙÙ Ø¹ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙØªØ¹Ø±ÙÙÙ ÙØ§ÙØ¥ÙØ§Ù Ø© ÙØ§ÙØ¹Ù Ù. ÙØ§ÙØ£ÙØ¯Ø§Ù Ù Ù Ø®Ø¯Ù Ø© Ø§ÙØªÙØ¬ÙÙ ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø§ÙÙ ÙØ§Ø±ÙØ© ÙÙ : 1) Ø§ÙØªØ¹Ø§Ø±Ù Ø¹ÙÙ Ø£ÙÙØ§Ø¹ Ø§ÙÙ ÙÙ ÙÙ ÙØ§ØµÙØ§ØªÙØ§ Ø 2) ØªØ¹ÙÙÙ Ø§ÙØ£Ù ÙÙØ§Øª ÙØ¨Ø±Ù Ø¬Ø© Ø§ÙÙ Ø³ØªÙØ¨ÙØ 3) Ø§ÙØ§ÙØªØ´Ø§Ù Ø¹Ù Ø§ØªØ¬Ø§ÙØ§Øª Ø§ÙØ£Ø¹Ù Ø§ÙØ 4) Â ØªÙÙÙÙ Ø§ÙÙ ÙØ§Ø±Ø§Øª ÙØ§ÙÙØ¯Ø±Ø§Øª ÙÙ ÙÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø¨Ø£ÙÙØ§Ø¹ Ø§ÙØ¹Ù Ù. Ø£Ù Ø§ Ù ÙØ§Ø¯ Ø§ÙØªÙØ¬ÙØ© ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø§ÙÙ ÙØ§Ø±ÙØ© ÙØ·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© ÙÙÙ Ù Ø°ÙÙØ±Ø© ÙÙ ÙØªØ§Ø¨ Ø§ÙØªÙØ¹ÙØ© ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø§ÙØ°Ù Ø£ØµØ¯Ø±ØªÙ ÙØ²Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØ´Ø¤ÙÙ Ø§ÙØ«ÙØ§ÙÙØ©. ÙÙÙØ·Ø¨Ù ÙØ´Ø§Ø· Ø§ÙØªÙØ¹ÙØ© ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø¨Ø·Ø±Ù Ù ØªÙÙØ¹Ø© ÙÙÙ : Ø¨Ø±ÙØ§Ù Ø¬ Ø§ÙØªÙØ¹ÙØ© ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø§ÙÙ ÙØ§Ø±ÙØ©Ø ÙØ§ÙØªÙØ¬ÙÙØ§ØªØ ÙØªØ¹ÙÙÙ Ø§ÙÙØØ¯Ø©Ø ÙØ§ÙÙÙÙ Ø§ÙÙ ÙØ§Ø±ÙØ ÙØ§ÙØ³ÙØ§ØØ© Ø§ÙÙ ÙØ§Ø±ÙØ©. Ø£Ù Ø§ Ø®Ø¯Ù Ø© Ø§ÙØªÙØ¹ÙØ© ÙØ§ÙØ§Ø³ØªØ´Ø§Ø±Ø© Ø§ÙÙ ÙØ§Ø±ÙØ© ÙÙ ØºØ±ÙØ© Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙØ¹Ù Ø·Ø±ÙÙ Ø§ÙØªÙØ¬ÙÙØ§Øª Ø§ÙØ¯Ø§Ø®ÙØ© ÙÙ Ø¹Ù ÙÙØ© Ø§ÙØªØ¯Ø±ÙØ³.